Importance of Native Grassland Habitat for Den-Site Selection of Indian Foxes in a Fragmented Landscape - Punjabi, Girish Arjun (Public Library of Science, 2013)
Fragmentation of native habitats is now a ubiquitous phenomenon affecting wildlife at various scales. We examined selection of den-sites (n = 26) by Indian foxes (Vulpes bengalensis) in a highly modified short-grassland landscape in central India (Jan-May, 2010). At the scale of the home-range, defined by an 800 m circular buffer around den sites, we examined the effect of land-cover edges and roads on selection of sites for denning using a distance-based approach. At the smaller den-area scale, defined by a 25 m x 25 m plot around den and paired available sites, the effect of microhabitat characteristics was examined using discrete-choice models. Indian foxes selected den-sites closer to native grasslands (t = -9.57, P < 0.001) and roads (t = -2.04, P = 0.05) than random at the home-range scale. At the smaller scale, abundance of rodents and higher visibility increased the odds of selection of a site by eight and four times respectively, indicating resource availability and predator avoidance to be important considerations for foxes. Indian foxes largely chose to den in human-made structures, indicated by the proportion of dens found in earthen bunds (0.69) and boulder piles (0.27) in the study area. With agricultural expansion and human modification threatening native short-grassland habitats, their conservation and effective management in human-dominated landscapes will benefit the Indian fox. The presence of some human-made structures within native grasslands would also be beneficial for this den-dependent species. We suggest future studies examine the impact of fragmentation and connectivity of grasslands on survival and reproductive success of the Indian fox.